1999
DOI: 10.1007/s004120050384
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear organization studied with the help of a hypotonic shift: its use permits hydrophilic molecules to enter into living cells

Abstract: A new procedure for introduction of hydrophilic molecules into living cells based on efficient uptake of these molecules into the cells during hypotonic treatment is presented and its use is demonstrated by a variety of applications. Experiments with cultured vertebrate and Drosophila cells and various animal tissues demonstrated that the increase in cell membrane permeability under hypotonic conditions is a general phenomenon in all animal cells tested. The efficiency of the method depends on the composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 29 publications
1
84
0
Order By: Relevance
“…In recent years, immunocytological methods have been developed for detecting newly synthesized RNAs within the cell using a BrUTP analog (Jackson et al+, 1993;Wansink et al+, 1993)+ These approaches have shown that transcription by RNA polymerase II is organized in discrete foci scattered throughout the nucleoplasm+ However, it has proven difficult to visualize the nucleolar transcription sites (Jackson et al+, 1993;Wansink et al+, 1993;Iborra et al+, 1996;Pombo et al+, 1999;Wei et al+, 1999)+ Unless special procedures are employed, the nucleolus remains unlabeled despite the high level of transcription within this organelle (Hadjiolov, 1985;Moss & Stefanovsky, 1995)+ Labeling of the nucleolus can be achieved by several methods+ RNA polymerase II inhibitors such as a-amanitin or DRB can be employed or, alternatively, RNA polymerase I-mediated transcription can be stimulated in a variety of ways (Jackson et al+, 1993;Wansink et al+, 1993;Hozak et al+, 1994)+ For example, NH 4 SO 4 has been added to the transcription medium (Jackson et al+, 1993) and Masson et al+ (1996) have reported that by removing glycerol from the permeabilization and transcription buffers and improving permeabilization with Triton X-100, it is possible to reveal RNA polymerase I transcription without the addition of inhibitors+ Recently, Koberna et al+ (1999) have shown that the use of a hypotonic shift procedure facilitates the uptake of BrUTP into the nucleolus+ However, all these experimental conditions perturb the cell integrity and may cause partial degradation of subcellular structures, leading to ultrastructural modifications as reported by some authors (Dundr & Raska, 1993;Masson et al+, 1996)+ In addition, the nucleolar labeling is always restricted to the synthetic sites and the transport of newly labeled rRNAs either within or from the nucleus to the cytoplasm has not yet been detected+…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, immunocytological methods have been developed for detecting newly synthesized RNAs within the cell using a BrUTP analog (Jackson et al+, 1993;Wansink et al+, 1993)+ These approaches have shown that transcription by RNA polymerase II is organized in discrete foci scattered throughout the nucleoplasm+ However, it has proven difficult to visualize the nucleolar transcription sites (Jackson et al+, 1993;Wansink et al+, 1993;Iborra et al+, 1996;Pombo et al+, 1999;Wei et al+, 1999)+ Unless special procedures are employed, the nucleolus remains unlabeled despite the high level of transcription within this organelle (Hadjiolov, 1985;Moss & Stefanovsky, 1995)+ Labeling of the nucleolus can be achieved by several methods+ RNA polymerase II inhibitors such as a-amanitin or DRB can be employed or, alternatively, RNA polymerase I-mediated transcription can be stimulated in a variety of ways (Jackson et al+, 1993;Wansink et al+, 1993;Hozak et al+, 1994)+ For example, NH 4 SO 4 has been added to the transcription medium (Jackson et al+, 1993) and Masson et al+ (1996) have reported that by removing glycerol from the permeabilization and transcription buffers and improving permeabilization with Triton X-100, it is possible to reveal RNA polymerase I transcription without the addition of inhibitors+ Recently, Koberna et al+ (1999) have shown that the use of a hypotonic shift procedure facilitates the uptake of BrUTP into the nucleolus+ However, all these experimental conditions perturb the cell integrity and may cause partial degradation of subcellular structures, leading to ultrastructural modifications as reported by some authors (Dundr & Raska, 1993;Masson et al+, 1996)+ In addition, the nucleolar labeling is always restricted to the synthetic sites and the transport of newly labeled rRNAs either within or from the nucleus to the cytoplasm has not yet been detected+…”
Section: Introductionmentioning
confidence: 99%
“…The cells were washed and dried. The detection of transcription signal in microinjected cells due to the incorporated bromouridine was performed as described in Koberna et al (1999). All washes were conducted with PBS, pH 7.4.…”
mentioning
confidence: 99%
“…Koberna et al 33 have also demonstrated that various fluorescent low-molecular weight compounds, such as nucleotides, peptides and dyes, are rapidly taken up by cell lines, a human primary cell culture, drosophila and xenopus cells, as well as slices of the rat liver by hypotonic shock. In contrast, the same molecules were not significantly internalized when the cells were exposed to an isotonic medium.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cultured cells were kept in a hypotonic medium for up to an hour without any loss of viability. 8 The second step of the hypotonic stress is the internalization of the excess plasma membrane from both the apical and the basolateral sides to reform the lost intracellular vesicles.…”
Section: Introductionmentioning
confidence: 99%